A simpler prescription for MHV graviton tree amplitudes in superstring theory - Ursulino, Tiago (Springer, 2013)
We extend the Berkovits-Maldacena prescription for MHV amplitudes of the open superstring to the closed superstring, showing that in the alpha'aEuro parts per thousand= 0 limit it reduces to the result of supergravity found recently by Hodges. We also verify that this prescription calculates the correct superstring tree level MHV amplitude for 4 gravitons including alpha' corrections.
Keywords: Scattering Amplitudes; Superstrings and Heterotic Strings; Extended Supersymmetry